The inexhaustible peasantry. Internal colonization and agricultural frontier movements in Nicaragua 1960-2010 (Tzintzun, Revista de Estudios Históricos, 2016)
The facts show that agricultural production of small properties is unfeasible inthe Third World. However, Nicaragua currently has an economic growth throughagriculture. This is a traditional peasant society that has colonized their territoryconstantly moving the farming frontier. What existing territorial characteristics inNicaragua allow in the xx1 century new agricultural frontier movements and in-tense internal migration? How has Nicaraguan agricultural space been since itsfounding as a nation to the present? Has the country been inserted in a process ofre-peasantry? To try to answer these and other questions, in this paper, as back-ground, there is a historical account of the territorial characteristics of Nicaragua.Subsequently, the characteristics of agro are presented during Somocismo and theimpact of agro-export model in the face of the country. In the second section theSandinista policies and population changes caused by the war are analyzed. Thethird section analyzes the processes of internal colonization in the postwar peri-od, and finally the current characteristics of Nicaraguan agriculture, the policiespursued set forh by Daniel Ortega to turn back Nicaragua into a more peasantsociety, control the economic activity and finally, limit movements within is ownagricultrual borders.
Keywords: agro-exportation; internal colonization; migration; agriculture